Social Networking Analysis - Chahar, Shalki (International Journal of Computer Sciences and Engineering, 2014)
In todayï¿½s day and age, a rapid proliferation of technology has enabled efficient global communication. As a result, the last decade has seen social networking emerge as the backbone of global interactions. At the kernel of this advent, lies the concept of networks. Networks are arrangements of interconnections among a variety of entities. From this we can deduce that social networks are social structures comprising individuals and the interactions they have with each other. The computational analysis of these networks is known as social network analysis.